2002
DOI: 10.1071/bt01017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat and smoke on germination of soil-stored seed in a south-eastern Australian sand heathland

Abstract: Various fire-related agents, including heat, smoke, ash and charred wood, have been shown to break dormancy and promote germination of soil-stored seed in a broad range of species in mediterranean-type systems. However, relatively little work has been conducted in south-eastern Australian heathlands. This study examined the effects of heat and smoked water on germination of the soil seed bank in a mature sand heathland within the Gippsland Lakes Coastal Park, in south-eastern Australia. Heat was clearly the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 35 publications
7
40
4
Order By: Relevance
“…The seedling density of heat-treated soil from the previous study at GP yielded 4575 seedlings m -2 (Wills and Read 2002), which was comparable with the 3111 seedlings m -2 from GP-24 in this study, and values from other heat-treated soil in Australian heathlands (Enright et al 1997;Marsden-Smedley et al 1997). However, in this study, seedling densities in control soils were substantially higher at GP-24 (1148 m -2 ) compared to the previous study (485 m -2 ) (Wills and Read 2002). The study by Wills (2002) indicated that seedling densities in heat-treated soil were almost ten times higher than those in the controls; however, in this study they were only ca.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The seedling density of heat-treated soil from the previous study at GP yielded 4575 seedlings m -2 (Wills and Read 2002), which was comparable with the 3111 seedlings m -2 from GP-24 in this study, and values from other heat-treated soil in Australian heathlands (Enright et al 1997;Marsden-Smedley et al 1997). However, in this study, seedling densities in control soils were substantially higher at GP-24 (1148 m -2 ) compared to the previous study (485 m -2 ) (Wills and Read 2002). The study by Wills (2002) indicated that seedling densities in heat-treated soil were almost ten times higher than those in the controls; however, in this study they were only ca.…”
Section: Discussionsupporting
confidence: 85%
“…This also allowed comparison of results with a previous soil seed bank study at one of the study sites, 'GP' (Wills and Read 2002). The previous study at GP used an application of smoked water and a heat treatment of 80-100°C to promote seed germination from soil cores (Wills and Read 2002). The results indicated no difference in mean species richness of the soil seed bank of smoketreated relative to control samples, while the heat treatment promoted germination in a significantly Plant Ecol (2007) 190:1-12 3 higher number of species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Centella asiatica and Bidens pilosa showed marked increases in emergence in response to heat. In contrast with studies from the Mediterranean region (Thanos et al 1992;Figueroa et al 2009;Moreira et al 2010) and Australia (Wills and Read 2002) where heat plays a major role in regulating post-fire emergence, smoke is perhaps the major fire-related factor in promoting seed germination and seedling emergence in the mesic Tall grassland of South Africa. The interaction of heat-shock and smoke also appears to be equally important (Keith 1997;Thomas et al 2007) in stimulating germination/ emergence of the species forming the mesic grassland soil seed bank (Thomas et al 2007).…”
Section: Discussioncontrasting
confidence: 51%
“…For instance, in south-eastern Australian sand heathland, Wills and Read (2002) recorded only 20 species. From species-rich Chilean Matorral soil seed bank samples Figueroa et al (2009) recorded only a total of 23 taxa.…”
Section: Discussionmentioning
confidence: 98%